2006
DOI: 10.1083/jcb.200511061
|View full text |Cite
|
Sign up to set email alerts
|

KIF14 and citron kinase act together to promote efficient cytokinesis

Abstract: Multiple mitotic kinesins and microtubule-associated proteins (MAPs) act in concert to direct cytokinesis (Glotzer, M. 2005. Science. 307:1735–1739). In anaphase cells, many of these proteins associate with an antiparallel array of microtubules termed the central spindle. The MAP and microtubule-bundling protein PRC1 (protein-regulating cytokinesis 1) is one of the key molecules required for the integrity of this structure (Jiang, W., G. Jimenez, N.J. Wells, T.J. Hope, G.M. Wahl, T. Hunter, and R. Fukunaga. 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
326
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(344 citation statements)
references
References 40 publications
(84 reference statements)
15
326
2
1
Order By: Relevance
“…(b) The same analysis performed in (a) was repeated on HeLa cells treated for 48 h with either control siRNA or with previously validated siRNAs designed on CIT-K mRNA 23 or KIF14. 15 In the case of CIT-K, similar results were obtained using previously validated shRNA-expressing plasmids 23 Statistical significance of differences in average was established using Student's two-tailed t-test. **Po0.01; ***Po0.001…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…(b) The same analysis performed in (a) was repeated on HeLa cells treated for 48 h with either control siRNA or with previously validated siRNAs designed on CIT-K mRNA 23 or KIF14. 15 In the case of CIT-K, similar results were obtained using previously validated shRNA-expressing plasmids 23 Statistical significance of differences in average was established using Student's two-tailed t-test. **Po0.01; ***Po0.001…”
Section: Resultsmentioning
confidence: 74%
“…Previous results indicated that the primary function of CIT-K, conserved from insects to mammals, is to promote the stability and the maturation of midbody before abscission. 15,[23][24][25] To assess whether this function may involve the stabilization of midbody microtubules, we measured the ratio of acetylated versus tyrosinated α-tubulin at the midbody of control cells and of cells lacking CIT-K. 28 Indeed, dynamic microtubules contain a relatively high amount of α-tubulin tyrosinated at its carboxyterminus, whereas stable microtubules show a high content of α-tubulin acetylated at the K40 residue. 29 We studied two cellular models characterized by different sensitivity to CIT-K loss and by different physiological relevance: cultures of proliferating neocortical neuronal progenitors obtained from control or from Cit-K knockout mice at embryonic day (E)12.5 and HeLa cells depleted of CIT-K by RNAi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations